DESAIN LINGKUNGAN PEMBELAJARAN PAI YANG MENDUKUNG INTERNALISASI NILAI-NILAI KEISLAMAN PADA KELAS IX DI SMP N19 MUARO JAMBI - aulia fadillah, Alya; Hayat, Najmul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of the Islamic Religious Education (IRE) learning environment in supporting the process of internalizing Islamic values among students in schools. Based on the results of preliminary observations at SMP Negeri 19 Muaro Jambi, several challenges were identified, such as low student participation in religious activities, a lack of exposure to Islamic culture, and suboptimal student motivation to learn. This study aims to examine the conditions of the PAI learning environment, identify factors that support and hinder the internalization of Islamic values, and formulate a design for the PAI learning environment that supports the development of religious character among ninth-grade students at SMP Negeri 19 Muaro Jambi. This study employs a descriptive qualitative approach, with research subjects comprising PAI teachers, ninth-grade students, and the school principal. Data collection techniques include observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that the PAI learning environment at SMP Negeri 19 Muaro Jambi has supported the internalization of Islamic values through habitual activities such as congregational prayer, group prayer, and Yasinan. However, implementation has not been optimal because there are still students who are less active in participating in religious activities. Supporting factors include the school’s religious vision, support from PAI teachers, and the school’s religious programs, while inhibiting factors include low student motivation, a lack of religious awareness, and limited practice of Islamic values within the family environment. An effective Islamic Education learning environment can be achieved through strengthening the Islamic school culture, teacher role modeling, contextual learning, and consistent religious activities